1969
DOI: 10.1099/0022-1317-5-4-463
|View full text |Cite
|
Sign up to set email alerts
|

Inapparent Persistent Virus Infection in Continuously Grown Aedes aegypti Mosquito Cells

Abstract: SUMMARYLong-term inapparent infections were established in continuously grown uncloned AYdes aegypti mosquito cells inoculated with Semliki Forest virus and incubated at 28 °. This response of mosqtlito cells to infection, which contrasts with the outcome of infection by the same virus of mammalian cells at 37 °, was due to a small proportion of virus-producing cells in the culture, and a low yield of virus per infected cell.The percentage of virus-producing cells was between 2.8 and 8 % at the height of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
2

Year Published

1973
1973
2005
2005

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 1 publication
2
30
0
2
Order By: Relevance
“…aegypti; posteriormente, se establecieron otras líneas celulares de esta misma especie obtenidas, en orden cronológico, por Singh en 1967 (10), Peleg en 1968 (11,12) (14)(15)(16)(17).…”
unclassified
“…aegypti; posteriormente, se establecieron otras líneas celulares de esta misma especie obtenidas, en orden cronológico, por Singh en 1967 (10), Peleg en 1968 (11,12) (14)(15)(16)(17).…”
unclassified
“…ever in the vertebrate cell infection results in cell death whereas in the mosquito cell the rate of cell division is unaltered and a persistent infection results (2,4,5).…”
mentioning
confidence: 99%
“…This relatively short period is in marked contrast to the 50-week interval reported by Igarashi (1979) for resistance to occur in dengue-1 PI cultures, indicating that we have not observed the same phenomenon. The possibility that the resistance is interferon-mediated is also unlikely, since the induction of resistance was not sensitive to actinomycin D. In addition, other investigators have shown that mosquito cells do not express interferon activity (Peleg, 1969;Murray & Morahan, 1973;Stollar & Shenk, 1973;Davey & Delgarno, 1974;Kascsak & Lyons, 1974).…”
Section: Simultaneous Infection Ofc6/36 Cells With Dengue-1 and Dengue-3mentioning
confidence: 99%